Publikasi Terindeks Scopus Oleh Pustakawan Indonesia, Apakah Jumlah Halaman Mempengaruhi Potensi akan Sitasi? - Prasetyo Adi Nugroho (THE LIGHT : Journal of Librarianship and Information Science, 2022)
Librarians should contribute through research and publications to develop their knowledge. Citation is a sign of showing popularity of a paper. This study aims to analyze the effect of the number of pages of a paper on the number of citations in Scopus indexed publications. This study uses 35 samples of secondary data that have been eliminated from 80 population data downloaded from Scopus. This study uses the OLS method to analyze the effect of variable X to variable Y. The results show that the prob. score. variable number of pages as variable X > 0.05, which means there is no effect on the number of citations as variable Y. paper quality determines whether a paper has the opportunity to be widely cited by other researchers or not. In addition, papers that have a large number of pages do not always have good quality content, so they do not always get the attention of other academics. Other content such as the uniqueness of the title, the regularity of the abstract, and the keywords that symbolize the content of the content also affect a paper to get a chance for citation.